2020
DOI: 10.1111/jvim.15910
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in dogs with localized splenic histiocytic sarcoma treated with splenectomy with or without adjuvant chemotherapy

Abstract: Background: Localized splenic histiocytic sarcoma (HS) in dogs is a poorly understood disease, and could have longer survival times than disseminated or hemophagocytic HS. Understanding the clinical behavior of localized splenic HS can refine treatment recommendations. Objective: To describe the clinical characteristics and outcomes of dogs with localized splenic HS. Animals: Fourteen client-owned dogs with histologically confirmed splenic HS that received splenectomy. Methods: Multi-institutional retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…39,40 Also, dogs with localised pulmonary or splenic HS had a MST of 432 and 427 days, respectively, when treated with curative-intent surgery and adjuvant CCNU chemotherapy. 41,42 However, when looking at a previously reported case of primary renal HS in a dog, survival time was shorter and the outcome similar to the present case. 19 In our case report, anaemia seemed to be related to disease progression.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…39,40 Also, dogs with localised pulmonary or splenic HS had a MST of 432 and 427 days, respectively, when treated with curative-intent surgery and adjuvant CCNU chemotherapy. 41,42 However, when looking at a previously reported case of primary renal HS in a dog, survival time was shorter and the outcome similar to the present case. 19 In our case report, anaemia seemed to be related to disease progression.…”
Section: Discussionsupporting
confidence: 73%
“…Dogs with localised forms of HS (lungs, skin, subcutaneous tissues, bone and joints) have been reported to have a longer survival time when treated with surgery and adjuvant chemotherapy/RT, while a study on periarticular HS without evidence of disseminated disease reported a median survival time (MST) of 980 days 39,40 . Also, dogs with localised pulmonary or splenic HS had a MST of 432 and 427 days, respectively, when treated with curative‐intent surgery and adjuvant CCNU chemotherapy 41,42 . However, when looking at a previously reported case of primary renal HS in a dog, survival time was shorter and the outcome similar to the present case 19 …”
Section: Discussionmentioning
confidence: 99%
“…While dogs with localized HS receiving multimodal treatments of surgery and chemotherapy could live longer than 1 year, [28][29][30] adjuvant lomustine did not provide any survival benefit in this cat.…”
Section: Discussionmentioning
confidence: 71%
“…Because of the highly aggressive nature of disseminated HS, effective treatment often requires both local (surgery and/or radiotherapy) and systemic (chemotherapy) treatment, even for localized forms 17 . Disseminated forms could be treated with systemic chemotherapy alone 3 .…”
Section: Discussionmentioning
confidence: 99%